What Does a Gamer Look Like? Video Games, Advertising, and Diversity. (January 2017) - Chess, Shira; Evans, Nathaniel J.; Baines, Joyya JaDawn
Recent years have seen changes to the video game industry and the image of video game players. There are more games on the market and a larger variety of ways to play those games. Yet, despite market shifts, authors such as Shaw demonstrate that there are still tensions surrounding gamer identification. Even as next-generation systems (such as the Xbox One, the PlayStation 4, and the Wii U) and casual gaming take hold of the market, tension remains between the perceptions of who is playing versus the reality of actual players. In our study, we perform a content analysis of video game commercials in 2013 to explore questions of diversity—particularly in terms of portrayals of the player's sex and ethnicity—to consider how the gamer is represented in terms of physical and behavioral attributes.